The Relationship Between Body Mass Index (BMI) and the Occurrence of Gastroesophageal Reflux Disease (GERD) Among Students of the Faculty of Medicine, Universitas Sumatera Utara, Batch of 2021 and 2022 (Sumatera Medical Journal, 2025)
Background: Gastroesophageal Reflux Disease (GERD) is a common digestive disorder, especially among young adults like college students. One factor linked to GERD is Body Mass Index (BMI). Although higher BMI is associated with a greater risk of GERD, limited data exists on this relationship in university populations, particularly at the Faculty of Medicine, Universitas Sumatera Utara. Objective: This study aims to analyze the relationship between BMI and GERD incidence in FK USU students from the 2021 and 2022 batches. Methods: An analytical, cross-sectional study was conducted using simple random sampling. The subjects were Medical Education students from the 2021 and 2022 batches. Data collection was done through direct distribution of the GERD-Q questionnaire. Statistical analysis included univariate and bivariate methods using chi-square tests. Results: Among 100 respondents, 52 (52.0%) had GERD. Among those with GERD, 43 (29.6%) were obese and 9 (22.4%) had normal BMI. Of those without GERD, 34 (20.6%) had normal BMI and 14 (27.4%) were obese. A significant relationship was found between BMI and GERD (p = 0.011). Conclusion: There is a significant relationship between BMI and GERD incidence among FK USU Medical Faculty students from the 2021–2022 batches.